Ethnobotany of the Caucasus - Bussmann, Rainer (Springer, 2017)
The Caucasus MRW (online and print) Volume will cover this European Macroregion. The content will focus on the ethnobotany of wild plants in this Macroregion and it will be first developed as an online site and, later, when all of the planned topics have been covered for this specific volume, printed in a hard copy version. The online site will remain live and be available for updates (with new monographs [if not covered initially due to lack of research]). The content will be divided into sections covering countries (or groups of countries), based on plant diversity and not necessarily political or national boundaries. The Caucasus volume will have an Introduction (4,000-6,000 words); 50 200 plant monographs (10 to maximum 50 monographs per country) with each monograph having a length of 1,500 words (with references), plus 2-4 photographs. To further define the content, the plant monographs will be divided into five major categories (food; medicine/cosmetic; veterinary; handicraft plants; and ritual/folkloric uses) and include notes. The number of the monographs in every category will be negotiated depending on the advances of the ethnobotanical research in each specific country, or group of countries. The main criteria for the inclusion of a given plant will be its cultural salience within a given country (assessed by the Volume Editor). References will be given at the end of the Introduction and each monograph.
Keywords: Ethnobotany -- Caucasus.; Caucasus.; elektronické knihy; electronic books